Nanofibrillar Collagen Scaffold Enhances Edema Reduction and Formation of New Lymphatic Collectors after Lymphedema Surgery. Issue 6 (December 2021) - Nguyen, Dung H.; Zhou, Anna; Posternak, Victoria; Rochlin, Danielle H.
Abstract : Background: Treatment of secondary lymphedema remains challenging, with suboptimal rates of edema reduction following physiologic procedures (i.e., lymphaticovenous anastomosis and vascularized lymph node transfer). The objective of this study was to investigate the long-term effect of a nanofibrillar collagen scaffold on edema reduction in lymphedema patients treated with lymphaticovenous anastomosis or vascularized lymph node transfer. Methods: A retrospective cohort study was performed, comparing stage 1 to 3 lymphedema patients who underwent lymphaticovenous anastomosis and/or vascularized lymph node transfer with or without delayed implantation of nanofibrillar collagen scaffold (BioBridge) from 2016 to 2019. The primary endpoint was excess volume reduction. Indocyanine green lymphatic mapping was performed to evaluate superficial lymphatic flow. Results: Edema reduction was significantly greater for the BioBridge cohort (12-month follow-up, n = 18) compared to controls (18.2-month follow-up, n = 11) (111.5 ± 34.5 percent versus 70.0 ± 19.0 percent; p = 0.0004). This held true in lymphaticovenous anastomosis and vascularized lymph node transfer subgroup analysis. The average rate of edema reduction increased by 3.5-fold in lymphaticovenous anastomosis and 7.6-fold in vascularized lymph node transfer following BioBridge placement. Eighty-eight percent of patients with concurrent liposuction and BioBridge implantation maintained normal volumes at 13 months postoperatively. Lymphatic mapping following BioBridge placement showed significantly more new lymphatic collectors and decreased dermal backflow. The majority of patients (77.8 percent) achieved and maintained normal limb volume at an average total follow-up of 29 months. Conclusion: Nanofibrillar collagen scaffold implantation enhances overall effectiveness of physiologic procedures, even in the presence of liposuction, and is a promising adjunct therapy for treatment of lymphedema. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.